The Implications of International Law in the South Africa vs. Israel Case: An Analysis of the Genocide Convention and the Role of the International Court of Justice - Nur Fadli S; Mira Nila Kusuma Dewi; Alif Nunqy Bellatrix; Andi Risal; M. Fahril Hidayat; Fikram F; Fatrah F (Madani: Jurnal Ilmiah Multidisiplin, 2026)
International law is often perceived as an idealistic framework separate from the harsh realities of politics. The case of South Africa versus Israel at the International Court of Justice (ICJ) from late 2023 to early 2024 highlights the relevance of international legal principles amid armed conflict. This study analyzes the legal and political implications of the judicial process, focusing on the application of the 1948 Genocide Convention, the role of the International Court, and the limitations of global law enforcement. The analysis shows that although the ICJ lacks the military power to enforce its rulings, the international legal process exerts significant moral, political, and diplomatic pressure. The case also reinforces global accountability and underscores the importance of international humanitarian law principles in the context of complex armed conflicts.